The Impact of Company Income Tax and Petroleum Profit Tax on the Profitability of Listed Oil and Gas Firms in Nigeria - Timothy Aondona Aondover (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2025)
This conceptual paper examined the impact of company income tax (CIT) and petroleum profit tax (PPT) on the profitability of listed oil and gas firms in Nigeria. These taxes are integral to Nigeria’s tax structure, especially for oil and gas companies that contribute significantly to the nation’s revenue. The paper provides a theoretical framework to analyze the relationships between taxation and profitability, proposing how these taxes might affect the performance of these firms. Drawing from existing literature, the study aims to explore key mechanisms through which CIT and PPT influence profitability, such as tax burden, operational efficiency, investment decisions, and capital structure. The research was conducted against the backdrop of the increasing importance of the oil and gas industry in the Nigerian economy and the need to understand how government taxation policies affect the profitability of companies in the sector. The paper argues that company income tax and petroleum profit tax have a significant negative impact on the profitability of listed oil and gas firms in Nigeria. This suggests that higher tax rates imposed by the government can hinder the profitability of companies in the industry. Therefore, it is recommended that the government review its tax policies for the oil and gas industry in Nigeria, taking into consideration the impact on the profitability of listed firms. This will not only lead to a more conducive business environment for these companies but also ensure sustainable economic growth for the country.